Peningkatan Kinerja Kepala Madrasah Ibtidaiyah Negeri Dan Swasta Di Kota Jayapura Melalui Fungsi Pengawasan Pengawas - Sutinah, Sutinah (Jurnal Pendidikan Indonesia, 2023)
This study discusses the efforts of supervisors in improving the performance of madrasah principals through the supervisory function of supervisors in madrasah Ibtidaiyah in Jayapura city. The purpose of this study was to determine the function of supervisors in improving the performance of madrasah principals in state and private madrasahs in Jayapura city. The method used in this research is a qualitative research method using psychological approaches and pedagogical approaches. The data sources in this study consisted of madrasah heads, K3MI Chairpersons, KKG Chairpersons, teachers, and other data sources in the form of important documentation regarding madrasah profiles, madrasah head data other educational support elements. This study concludes that, the supervisory function of Madrasah supervisors in improving the performance of public and private madrasah principals in Jayapura City has not gone well so it needs maximum efforts to improve it by planning, implementing, and evaluating supervision programs and providing guidance and training in the form of both academic coaching and managerial coaching. The results of this study indicate that the supervisory function of supervisors in improving the performance of madrasah heads in MI Jayapura city during the implementation of tasks with reference to coaching academic, managerial and extracurricular activities has been evenly distributed. With the efforts made by the supervisor by providing guidance, motivation and encouragement, the madrasah heads finally made changes for the better in managing the education units they manage.